Chronic deep brain stimulation of the human nucleus accumbens region disrupts the stability of intertemporal preferences - Wagner, Ben; Schüller, Canan B.; Schüller, Thomas; Baldermann, Juan C.; Kohl, Sina; Visser-Vandewalle, Veerle; Huys, Daniel; Marx, Milena; Kuhn, Jens; Peters, Jan (The journal of neuroscience, 2023)
When choosing between rewards that differ in temporal proximity (intertemporal choice), human preferences are typically stable, constituting a clinically relevant transdiagnostic trait. Here we show, in female and male human patients undergoing deep brain stimulation (DBS) of the anterior limb of the internal capsule/NAcc region for treatment-resistant obsessive-compulsive disorder, that long-term chronic (but not phasic) DBS disrupts intertemporal preferences. Hierarchical Bayesian modeling accounting for temporal discounting behavior across multiple time points allowed us to assess both short-term and long-term reliability of intertemporal choice. In controls, temporal discounting was highly reliable, both long-term (6 months) and short-term (1 week). In contrast, in patients undergoing DBS, short-term reliability was high, but long-term reliability (6 months) was severely disrupted. Control analyses confirmed that this effect was not because of range restriction, the presence of obsessive-compulsive disorder symptoms or group differences in choice stochasticity. Model-agnostic between- and within-subject analyses confirmed this effect. These findings provide initial evidence for long-term modulation of cognitive function via DBS and highlight a potential contribution of the human NAcc region to intertemporal preference stability over time. - SIGNIFICANCE STATEMENT Choosing between rewards that differ in temporal proximity is in part a stable trait with relevance for many mental disorders, and depends on prefrontal regions and regions of the dopamine system. Here we show that chronic deep brain stimulation of the human anterior limb of the internal capsule/NAcc region for treatment-resistant obsessive-compulsive disorder disrupts the stability of intertemporal preferences. These findings show that chronic stimulation of one of the brain's central motivational hubs can disrupt preferences thought to depend on this circuit.